Luwians. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2003)
The Luwians played at least as important a role as the Hittites in the history of the Ancient Near East during the second and first millennia BCE, but for various reasons they have been overshadowed by and even confused with their more famous relatives and neighbours. Redressing this imbalance, the present volume by an international team of scholars offers a comprehensive, state-of-the-art appraisal of the Luwians, the first of its kind in English. A brief introduction sets the context and confronts the problem of defining 'the Luwians'. Following chapters describe their prehistory, history, writing and language, religion, and material culture.